"Waiting for Science to Catch up with Practice": an examination of 10-year YouTube trends in discussions of chronic cerebral spinal venous insufficiency treatment for multiple sclerosis. (2nd October 2019) - Hynes, Sinéad M.; Ghahari, Setareh; Forwell, Susan J.
ABSTRACT: Objective : The objective of this longitudinal study examined, first, whether people with multiple sclerosis who previously advocated for angioplasty to treat chronic cerebral spinal venous insufficiency (CCSVI) through YouTube continued reporting benefits. Second, it examined a new cohort reporting on CCSVI treatment, and third, whether perspectives have changed. Method : YouTube videos from August 2011 to January 2019 related to CCSVI were retrieved. Once retrieved, all videos were compiled, classified and analyzed. Categorical data were reported and a pre-determined code-book was used to code videos. Data from the videos were extracted and analyzed using discourse analysis. Results : 1293 videos related to CCSVI were uploaded by 54 people with multiple sclerosis who met the inclusion criteria. YouTube videos uploaded by people with multiple sclerosis have shifted in volume and message. The initial surge in interest in CCSVI treatment has diminished, but there still exists strong advocates for its use. There appears to be an inconsistency between positive results, actual improvements in symptoms, and the overall messages reported. Very little long-term data was available as the procedure is relatively new. Conclusion : Practitioners may be faced with pressure to provide unproven treatments in the future and should be understanding but evidence-driven when supporting multiple sclerosis therapies.